RITUAL WULLAPODDU REPRESENTASI KEARIFAN HIDUP ETNIK WEWEWA DI PULAU SUMBA: DESKRIPSI AWAL PENDIDIKAN LINGKUNGAN DAN BAHASA RITUAL - Tualaka, Diaspora Markus (JURNAL TRITON PENDIDIKAN, 2016)
WullaPoddu (holy moon) is one of Merapu religious ritual presented by Wewewa etnics in Sumba island. During this holy moon all of Merapu religion prohibited to do some activities which can create instability toward human nature and the cosmos. This ritual performance based on traditional enumeration which dissimilar to month in messiah calendar but they appoint based on natural phenomena. In performing this ritual there are some materials which sacred by them and its have philosophical meaning. Some rules are determine by Rato (the ritual chief) must be obey by all the members of Merapu religious community. Knowledge system of the community is ethnoscientific religiously fashioned and united in all aspect of Wewewa community livelihood. Morals and noble values still relevant to develop in supporting social livelihood nowadays. Construing theory presented by Turner (1967) and ecolinguistic perspective presented by Haugen (1972) are used to interpreted the meaning and function of Wulla Poddu ritual. The philosophical meaning will become the noble values (as local genius) which is can be an inheritance for young generation of Wewewa ethnic specially and also as cultural property for Indonesian people.